PENGARUH SUPLEMENTASI BETAIN DALAM RANSUM RENDAH METIONIN TERHADAP KECERNAAN NUTRIEN PADA PUYUH (Coturnix coturnix japonica) - Gumilar, Gebby Citra Vasthu (Journal of Livestock Science and Production, 2018)
The research was aimed to determine the effect and optimum level of betaine suplementation in low methionine diet on nutrient digestibility of quail. This research used 340 quails aged in four weeks with a mean initial body weight 98.31± 8.67 g with CV 8.82%. The experimental diets were formulated with 0,3% methionine. The design of the experiment used completely randomized design with four treatments, each treatment was repeated five times. The treatments given were betaine supplementation as 0 (control), 0.07; 0.14 and 0.21%. In vivo digestibility was measured by total collection method, when the quails was at the age of 13 weeks. Two quails was randomly chosen from each replication. Nutrient digestibility data were analyzed using analysis of variance and if there was the effect of treatment, then it was followed orthogonal polymonial test. The results of analysis of variance showed that the highest level of betain in feed increased the digestibility of crude protein with the regresion equation y =16.7717 + 69.7569x (R2=0.37) and optimum level of betaine supplementation on crude ash digestibility used the regression equation y = 6.7546x + 132.624 -500.806x2 (R2=0.21) was 0.13%. The conclusion of this research was that betaine supplementation in low methionine diet increased digestibility of crude protein and crude ash. Keywords: betaine, methionine, nutrient digestibility, quail